«I miei versi, più che letti, sono fatti per essere cantati» - basei, matilde (Quaderni Veneti, 2016)
In a synergistic background between different arts, the Pascoli’s attention to sound in his compositions, mainly in poetry, and the artifices which the poet employs to highlight his passion for musicality are recalled. Because of their attractive sonority, his work aroused the composers’ interest, mostly in his time, an age in which it was customary, to music poems written by significant authors; one of them was Guido Alberto Fano, a fine artist born in Padua in 1875. Fano’s work for setting in music «Il sogno della vergine», «Nebbia» and «La mia sera», experimenting with melodic innovations but respecting the original poetic texts is described in the brief article.